Compreensão da evolução das encostas do médio vale do rio Marrecas (planalto basáltico - SW PR) através da caracterização de depósitos de colúvio - Geremia, Francielli (2009)
The object of this research is to understand the evolution of the slopes of the middle valley of Marrecas River, established in basaltic rocks, located in southwestern of Paraná state, through the characterization of two colluvial deposits. Colluviums deposits are set on the slopes of the urban area in Francisco Beltrão, one of them located in the Hill of Calvary and the other one in the hill of São Cristóvão district. Descriptions were carried out of stratigraphic sections and analysis of granulometry, mineralogy of fractionated clay and micromorphological (micro factory ). In the neighborhood of São Cristóvão three colluvial units were identified: i) Unit I, located at the base of the section, massive crushed rock mud ii) Unit II, massive muddy gravel and iii) Unit III massive crushed rock mud. On the other hand, on the section of the Hill of Calvary four colluvial units were identified: i) Unit I, muddy gravel with supported matrix and massive structure and ii) Unit II, muddy gravel with massive structure, iii) Unit III, muddy gravel with massive clasts supported and iv) unit IV, similar to Unit II. It is suggested that the colluvial units were generated by movements of mass like landslides / slips, with flows of high concentration of water and sediment. Two types of mass movements were individualized: a) the flow of land for units I and III of the section São Cristóvão and units II and IV of the section Hill of Calvary, and b) flow of debris for unit II of Sao Cristóvão section and unit I of the Hill of Calvary. The analysis of the micro factory / micromorphology of the colluvial units exhibited predominantly porphyritic matrix with microstructure on cracks and locally in blocks. It is suggested that the slope of the neighborhood of São Cristóvão, it was exposed for a significant time, the weathering causing the lateritic soil profile (ferruginous or fersialitico) to develop. On the slope of the Hill of Calvary the superficial surface is shallower due to the higher frequency of action of the superficial runoff before the mass movements. Both the colluvial deposits of the slopes studied record the prevalence of events of morphogenesis in the last stages of evolution, thus promoting the retreat of the slopes due to exceptional rainfall events. The study of evolutionary phenomena in two slopes of the middle valley of Marrecas River suggests that the morphogenesis appeared in the scale of the middle valley of Marrecas River, being the last events associated with the expansion of valleys and retreat of slopes. The question is whether other slopes had also experienced the environmental instability and presented superficial formation correlated to the slopes studied